The Effects of An Active Listening Technique on The Nursesâ Empathy Abilities in Giving Nursing Services in Surabaya - Heriyanto, Bambang; Cahyono, Intim; Tumini, Tumini (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
Nursing service given to a patient will be excellent if the nurse shows her empathy to the patient. The objective of this present research was to analyze the effects of  the active listening technique on the nursesâ emphatic ability in giving a nursing service in the hospital Soewandhi, Surabaya. It was a quasi-experimental  type with non randomized control group, pretest-posttest design.  The population were all nurses in the hospital Soewandhi and the sample was taken randomly. The data were descriptively  and inferentially analyzed using the Wilcoxon and Mann-Whitney Test with the level of significance of 0.05. The results showed that  the change of the total mean score in the emphatic abilities in the  control group before and after the intervention was insignificant with the p-value of 0.262.  The intervention group showed a change of the total mean score  in the emphatic abilities before and after the intervention with the p-value of 0.000. Meanwhile,  among the control groups with intervention, a significant difference  was shown with the p-value of 0.001.  The nurses   trained in the application of  the active listening technique showed  better empathy abilities than those who did not get any training.